Cobalt and Nitrogen Co-Doped Peat Derived Carbon Based Catalysts for Oxygen Reduction. (25th June 2020) - Jäger, Rutha; Teppor, Patrick; Härk, Eneli; Härmas, Meelis; Adamson, Anu; Paalo, Maarja; Volobujeva, Olga; Kikas, Arvo; Kochovski, Zdravko; Romann, Tavo; Härmas, Riinu; Lust, Enn
Abstract : Using different carbonization protocols, five peat derived carbon materials were synthesized. These carbons have very different surface morphology confirmed by HR-SEM and different porosities and pore size distributions obtained by N2 sorption method. The ORR activity of the peat derived carbons also differs significantly in 0.1 M HClO4 solution. Additionally, co-doping the peat derived carbons with cobalt and nitrogen enhanced their catalytic activity considerably. The most active ORR catalyst was achieved using the carbon support where the dry milled peat was mixed with ZnCl2 and pyrolyzed in Ar for 2 h at 700 °C. Interestingly, the activity of the initial carbon powder does not seem to be a clear indicator of the final activity of the M-N/C catalysts synthesized from it.